On Fixed Points in Quasi Partial b-Metric Spaces and an Application to Dynamic Programming: Hassen Aydi, Abdelbasset Felhi, Slah Sahmim - Team, Support (Thai Journal of Mathematics, 2021)
In this paper, we prove several fixed point results in quasi partial b-metric spaces. We derive some consequences and corollaries from our obtained results. Some examples are presented making effective the new concepts and results. An application on dynamic programming is also provided.